Awareness of the Spectrum Condition of Autism among Pre-Primary School Teachers in Western Kenya - Sadia, Moses; Ayodo, George; Amimo, Fred; Itotia, Serah; Obinju, Christine; Ściborski, Romuald J. (African Journal of Health Sciences, 2023)
Autism is a spectrum of neurodevelopmental disorders exhibited in early childhood with variable manifestations as children grow up. However, the level of awareness of the condition is poorly understood among pre-primary school teachers. This study, therefore, assessed the awareness of the spectrum condition of autism among pre-primary school teachers in western Kenya. A descriptive cross-sectional study design was employed and data collected from 321 participants using semi-structured questionnaires and Key Informant interviews. The participants were selected using purposive sampling. The quantitative data were analyzed using SPSS version 20 and qualitative data analyzed thematically. The response rate was 76.9% with 16.8% (41) males and 83.2% (203) females. A total of 41.5% (n=110) of the teachers had never heard of autism. Of all teachers who had heard of autism, 100% (7) were from special needs schools, and 64.4% (67) and 45.1% (60) were from public and private schools, respectively. About 78.8% (105) of teachers perceived autism as a neurodevelopmental disability and academically challenged children, 15% (20) as a psychiatric illness similar to madness, 4.5% (6) as spiritual affliction/demon-possessed children and 1.5% (2) as parental neglected children. This study shows that pre-primary school teachers have inadequate awareness of the spectrum condition of autism, and this limits educational service delivery. This study therefore recommends special training for pre-primary school teachers and improvement of the curriculum and training to include the spectrum condition of autism.
Keywords: Autism Spectrum Disorder (ASD); Education; Early Childhood Education; Educators; Teacher Training